2021
DOI: 10.1371/journal.pone.0254750
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature on host patch exploitation by an egg parasitoid

Abstract: The effect of temperature during host patch exploitation by parasitoids remains poorly understood, despite its importance on female reproductive success. Under laboratory conditions, we explored the behaviour of Anaphes listronoti, an egg parasitoid of the carrot weevil, Listronotus oregonensis, when foraging on a host patch at five temperatures. Temperature had a strong effect on the female tendency to exploit the patch: A. listronoti females parasitized more eggs at intermediate temperature (20 to 30°C) comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Thus, besides variation in developmental rates among temperatures, community contexts, and species, other factors contribute to differences in effects of phenological shifts across treatments. For example, preference and the ability to locate prey of different developmental stages of higher quality could also modify outcomes of host‐parasitoid interactions under warming (Augustin et al, 2021; Moiroux et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, besides variation in developmental rates among temperatures, community contexts, and species, other factors contribute to differences in effects of phenological shifts across treatments. For example, preference and the ability to locate prey of different developmental stages of higher quality could also modify outcomes of host‐parasitoid interactions under warming (Augustin et al, 2021; Moiroux et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Anagrus delicatus can spread the risk of increased mortality by ovipositing fewer eggs in each patch even if more suitable hosts are available ( Reeve et al 1994 ). Augustin et al (2021) showed that patch time allocation in Anaphes listronoti Huber (Hymenoptera: Mymaridae) decreased when temperature increased, although the patch-leaving rules were not affected. In the context of climate change, even a single extreme unreliable event with strong temperature variation can have a major impact on host mortality, increasing the variability of host richness and/or travel times between patches.…”
Section: Behaviormentioning
confidence: 99%
“…Empirical studies on the patch-leaving behaviour of egg and pupal parasitoids, motivated by the marginal value theorem, typically used a mass of hosts or a small area ( e.g., ≈ 1.5 cm 2 ) containing hosts as a patch of hosts (Field 1998; Wajnberg et al 2006; Augustin et al 2021; Zhang et al 2022). The marginal value theorem’s explanation for partial patch exploitation in these settings is related to functional response because within-patch parasitism is described by a functional response model.…”
Section: Introductionmentioning
confidence: 99%
“…However, given that hosts were located next to each other, it is difficult to consider that parasitoids left a patch because it was too difficult to find other hosts. In fact, direct observations of parasitoids in these studies revealed that parasitoids left a patch without parasitising healthy hosts that were physically encountered (Wajnberg et al 2006; Augustin et al 2021; Zhang et al 2022).…”
Section: Introductionmentioning
confidence: 99%